THE KEY RATE OF THE CENTRAL BANK AS A MONETARY POLICY TOOL - HARKUSHA, Yuliya; IVANOVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the theoretical and methodological foundations of the interest policy of the National Bank of Ukraine. It is noted that the accounting rate is one of the monetary instruments, with the help of which the central bank establishes for banks and other subjects of the money market a benchmark for the value of the funds raised and placed. It was determined that in the process of implementing the interest policy, the National Regulator also sets the interest rate for permanent access instruments from: absorption of excess liquidity for the overnight term (for overnight deposit certificates) at the level of the discount rate; provision of additional liquidity for the overnight term (for overnight loans) linked to the discount rate. The study also states that the interest rate channel is the main channel of the transmission mechanism, because the mechanism of its action is that a change in monetary policy through a change in the discount rate directly affects short-term rates on the financial market, and through the yield curve - on long-term rates. The importance of returning to the inflation targeting regime, choosing its eclectic type, has been proven under favorable conditions. This will make it possible to apply a double mandate: ensuring price stability and, for example, maintaining the employment of the population. After all, full-fledged inflation targeting requires a sufficient level of development of the financial market, balanced state finances, an appropriate structure of the economy (free pricing, an insignificant level of dollarization of the economy, etc.). Also, under appropriate conditions, it is necessary to restore the symmetric corridor of interest rates and return to the operational design of the interest policy, which was in effect before the introduction of martial law.
Keywords: central bank; monetary policy; interest rate policy; monetary policy instruments; discount rate